2013
DOI: 10.1021/jp407914f
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Oxides Change the Atmospheric Reactivity of Soot: NO2 Uptake under Dark and UV Irradiation Conditions

Abstract: The heterogeneous reactions between trace gases and aerosol surfaces have been widely studied over the past decades, revealing the crucial role of these reactions in atmospheric chemistry. However, existing knowledge on the reactivity of mixed aerosols is limited, even though they have been observed in field measurements. In the current study, the heterogeneous interaction of NO2 with solid surfaces of Al2O3 covered with kerosene soot was investigated under dark conditions and in the presence of UV light. Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 79 publications
2
22
0
Order By: Relevance
“…A number of laboratory studies have supported this reaction, with HONO yields varying between 20-100 % depending on the fuel type used to generate the soot, initial NO2 concentrations and soot coatings (Arens et al, 2001;Aubin and Abbatt, 2007;Gerecke et al, 1998;Guan et al, 2017;Khalizov et al, 2010;Kleffmann et al, 1999;Lelièvre et al, 2004;Romanias et al, 2013;Stadler and Rossi, 2000). An observation that is consistent across many laboratory experiments is that the uptake of NO2…”
Section: Introductionmentioning
confidence: 72%
“…A number of laboratory studies have supported this reaction, with HONO yields varying between 20-100 % depending on the fuel type used to generate the soot, initial NO2 concentrations and soot coatings (Arens et al, 2001;Aubin and Abbatt, 2007;Gerecke et al, 1998;Guan et al, 2017;Khalizov et al, 2010;Kleffmann et al, 1999;Lelièvre et al, 2004;Romanias et al, 2013;Stadler and Rossi, 2000). An observation that is consistent across many laboratory experiments is that the uptake of NO2…”
Section: Introductionmentioning
confidence: 72%
“…It is likely that wet surfaces inside the tunnel, as a result of spray from tyres, resulted in a loss of HONO. The Henry's law constant (in water) of HONO (k H = 4.8 × 10 −1 mol m −3 Pa −1 ) is approximately 4800 times greater than that of NO 2 (k H = 9.9 × 10 −5 mol m −3 Pa −1 ) (Sander, 2015), and therefore HONO is likely to be washed out more rapidly than NO 2 on wet surfaces, resulting in a reduction in the HONO/NO x ratios. As a result, this precipitation event was excluded from the final dataset for calculation of emission ratios.…”
Section: Instrumental Techniquesmentioning
confidence: 90%
“…Note that similar absorption spectra were recorded in the literature. 8,22 Al 2 O 3 is not a semiconductor material. Thus, it cannot directly initiate a sequence of redox reactions, such as TiO 2 and Fe 2 O 3 ; however, it may assist and enhance a photochemical process.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 In particular, Kim et al have observed that mineral dust originated from North China after long-range transportation over polluted areas, was enriched with substantial concentrations of elemental and organic carbon. 7 It has been proposed that this "mixing process" can affect the optical properties 7,8 and hygroscopicity of the aerosol particles. 9 Hence, they could affect the radiation balance of the planet.…”
Section: Introductionmentioning
confidence: 99%